Progressive dysarthria and ataxia - Lynsey McAlpine; Fiona Cran; Eluzai Hakim (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
'Guillain-Barre syndrome' (GBS) is a broad term used to describe a collection of clinical syndromes which manifest as acute immune-mediated demyelinating diseases or more rarely axonal diseases of the peripheral nervous system. The most commonly recognised form is 'acute inflammatory demyelinating polyradiculoneuropathy' (AIDP), which classically presents as a proximal and distal weakness with diminished reflexes, often involving the cranial nerves and muscles of respiration [1]. It is a neurological emergency as these patients are at risk of developing respiratory failure; one third will require admission to the Intensive Care Unit (ICU) for ventilatory support, and mortality rates of 3-10% have been reported